Analysis of Factors Related to the Head of the Nurses in the Implementation of Prevention and Control of Infections in the Hospital - Serri Hutahaean; Nourmayansa Vidya Anggraini; Dosmaida Nababan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The problem of infection in nursing services in the hospital and in health care facilities is that Healthcare-associated infections are still high. The compliance rate in implementing Infection Prevention and Control is still low. Nurses' non-compliance with Infection Prevention and Control implementation can be found in the ward with a variety of causative factors. This study aims to analyze the factors associated with nurse compliance in implementing infection prevention and control in the hospital. The method used was quantitative research with a cross-sectional design. The respondents consisted of 34 implementing nurses at hospital X in Jakarta. The results showed a significant relationship between nurses 'knowledge (pv 0.01; α 0.05), motivation, (pv 0.04; α 0.05) and nurses' perceptions (pv 0.02; α 0.05) on adherence Infection Prevention and Control implementation, but there is no relationship between attitude factor with the implementation of Infection Prevention and Control (pv 0.51; α 0.05). It is suggested that the support of nursing management, the head of room and service providers are needed to improve nurses' compliance with the implementation of Infection Prevention and Control as a basis for improving the quality of nursing services in hospitals through increasing the knowledge, motivation, and perceptions of nurses in the provision of facilities and infrastructure in infection prevention and control.